High‐explosive generators of dense low‐temperature plasma for proton radiography. Issue 2 (4th January 2018) - Mintsev, V.B.; Shilkin, N.S.; Ternovoi, V.Ya.; Nikolaev, D.N.; Yuriev, D.S.; Golubev, A.A.; Kantsyrev, A.V.; Skobliakov, A.V.; Bogdanov, A.V.; Varentsov, D.V.; Hoffmann, D.H.H.
Abstract : The article reviews the design and physical applications of high‐explosive generators for dense low‐temperature plasma. The PUMA proton microscope with magnetic optics at the Institute for Theoretical and Experimental Physics by A.I. Alikhanov of National Research Centre «Kurchatov Institute» (Moscow, Russia) was used to diagnose the plasma. The generators were developed for measurements of the equation of state of non‐ideal plasma, investigation of phase transitions in hydrogen or molecular gases, and studies of the properties of the interior of Giant planets. A proposal was made to repeat the experiments with explosive generators using the proton microscope PRIOR (Proton Microscope for Facility for Anti‐proton and Ion Research) at the GSI Helmholtzzentrum fur Schwerionenforschung (Darmstadt, Germany) and at the designed proton microscope at the Institute for Nuclear Research (Troitsk, Russia).